Nutritional aspects in autoimmune diseases undergoing hematopoietic stem cell transplantation: overview and recommendations on behalf of the EBMT ADWP and Nurses Group - Gandossi, Chiara; Jessop, Helen; Hahn, Anne; Heininger, Lisa; Henes, Jörg; Radaelli, Alexia Marina; Carmagnola, Anna; Morello, Enrico; Renica, Chiara; Bertulli, Alice; Lazzari, Lorenzo; Kenyon, Michelle; et al. (Frontiers in Nutrition, 2024)
Autoimmune diseases (ADs) represent a heterogeneous group of conditions affecting 5 to 10% of the global population. In recent decades, hematopoietic stem cell transplant (HSCT), mainly autologous, has been successfully adopted to treat patients affected by severe/refractory ADs. In this context malnutrition has a detrimental impact on relapse, mortality, infection rate, engraftment, long-term survival, and prolongation of hospitalization. However, in this population, the management of nutrition should be improved since nutritional assessment is partially performed in routine clinical practice. A panel of nurses and physicians from the European Society for Blood and Marrow Transplantation (EBMT) reviewed all available evidence based on current literature and expert practices from centers with extensive experience in HSCT for ADs, on the nutritional management of ADs patients during HSCT procedure. In this context, adequate nutritional status predicts a better response to treatment and improves quality of life. Herein, a systematic and comprehensive monitoring of nutritional status before, during and after HSCT, with adequate nutritional support in the case of ADs patients, in addition to assessing the dietary requirements associated with HSCT has been covered. Moreover, given the singularity of each AD, the underlying disease should be considered for an appropriate approach. The management and evaluation of nutritional status must be carried out by a multidisciplinary team to assess the needs, monitor the effectiveness of each intervention, and prevent complications, especially in complex situations as patients affected by ADs.